Sosialisasi Peran Pemuda-Pemudi dalam Pemilihan Umum (PEMILU) di Nagan Raya Tahun 2019 - Yeni Sri Lestari; Irma Juraida; Triyanto Triyanto; Dara Quthni Effida (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
Problems in the field show that there is a lack of awareness of young people in the realm of political education. In this case, political education in question is the lack of awareness and awareness of young people to be active and participate in giving their opinions and input to political issues so that they do not participate in the implementation of the General Election has raised challenging issues for the balance of a regional government system. . The implementation of this service is a socialization carried out face to face by delivering material related to the theme of devotion. The results and benefits obtained from the implementation of this socialization are able to foster early awareness of young people to start active in the political process such as exercising their voting rights when elections are held and able to provide motivation for young people to engage directly as a Success Team in supporting prospective couples who have vision-mission according to their views.